Comparative effect of treadmill exercise on mature BDNF production in control versus stroke rats. - Aurore Quirié; Marie Hervieu; Philippe Garnier; Céline Demougeot; Claude Mossiat; Nathalie Bertrand; Alain Martin; Christine Marie; Anne Prigent-Tessier (PLoS ONE, 2012)
Physical exercise constitutes an innovative strategy to treat deficits associated with stroke through the promotion of BDNF-dependent neuroplasticity. However, there is no consensus on the optimal intensity/duration of exercise. In addition, whether previous stroke changes the effect of exercise on the brain is not known. Therefore, the present study compared the effects of a clinically-relevant form of exercise on cerebral BDNF levels and localization in control versus stroke rats. For this purpose, treadmill exercise (0.3 m/s, 30 min/day, for 7 consecutive days) was started in rats with a cortical ischemic stroke after complete maturation of the lesion or in control rats. Sedentary rats were run in parallel. Mature and proBDNF levels were measured on the day following the last boot of exercise using Western blotting analysis. Total BDNF levels were simultaneously measured using ELISA tests. As compared to the striatum and the hippocampus, the cortex was the most responsive region to exercise. In this region, exercise resulted in a comparable increase in the production of mature BDNF in intact and stroke rats but increased proBDNF levels only in intact rats. Importantly, levels of mature BDNF and synaptophysin were strongly correlated. These changes in BDNF metabolism coincided with the appearance of intense BDNF labeling in the endothelium of cortical vessels. Notably, ELISA tests failed to detect changes in BDNF forms. Our results suggest that control beings can be used to find conditions of exercise that will result in increased mBDNF levels in stroke beings. They also suggest cerebral endothelium as a potential source of BDNF after exercise and highlight the importance to specifically measure the mature form of BDNF to assess BDNF-dependent plasticity in relation with exercise.